Pengaruh Edukasi Gizi dan Permainan Ular TangGiz terhadap Pengetahuan Gizi Siswa/i SMA PGRI 2 Kota Jambi - Wulansari, Arnati; Putri, Darin Aini Avian; Ramlah, Siti; Hayati, Indah Puji; Sari, Indah Permata; Septyani, Dhea Putri; Munawaroh, Novia; Zafira, Audi Fitri (Jurnal Abdimas Kesehatan (JAK), 2024)
Obesity is one of the most worrying health problems, especially for children and adolescents. Obesity in adolescents is caused by many factors, namely imbalanced diet, excess intake of macronutrients, frequent consumption of fast food, history of obesity in parents, and the habit of skipping breakfast. One of the causes of nutritional problems is due to lack of knowledge about nutrition which can then lead to mistakes in choosing food. Community service was carried out at SMA PGRI 2 Kota Jambi with 24 students as participants with an approach using an educational method with presentation (material presentation) and the game "Ular TangGiz". From the results obtained, there was an increase in knowledge about balanced nutrition and obesity in students of SMA PGRI 2 Kota Jambi. This is indicated by an increase or increase in the average pre-test to post-test score of 26.04%. This increase is proven by statistical tests using the Wilcoxon difference test method which obtained a small Asymp-sig result of 0.05, namely 0.00, which can be interpreted that there is a significant difference between the average results of the pre-test and post-test scores so that it can be said that there is an influence of the use of the presentation method and the "Ular TangGiz" game in Nutrition Education on increasing knowledge about balanced nutrition in students of SMA PGRI 2 Jambi City